Juvenile hormone signal transducer hairy inhibits Krüppel homolog1 expression. - He, Q.; Wang, S.; Chen, S.; Chen, J. (Biochemical and Biophysical Research Communications, 2024)
Hairy and Krüppel homolog 1 (Kr-h1) are transcriptional repressors that act synergistically to mediate the gene-repressive action of juvenile hormone (JH). However, whether a regulatory relationship exists between Hairy and Kr-h1 remains unclear. In this study, an inhibitory effect of Hairy on Kr-h1 expression was found. Genetic studies in Drosophila have shown that the simultaneous overexpression of Hairy and Kr-h1 can rescue the defective phenotypes caused by the overexpression of a single factor. Reduced expression of Kr-h1 was observed in Hairy-overexpressing flies and cells, whereas the expression levels of Hairy were unaffected in cells with ectopic expression of Kr-h1. The inhibitory effect of Hairy on Kr-h1 expression was found to occur at the transcriptional level, as Hairy bound directly to the B-box within the Kr-h1 promoter via the bHLH motif and recruited the corepressors C-terminal binding protein (CtBP) and Groucho (Gro) through the PLSLV and WRPW motifs, respectively. Our findings revealed a regulatory relationship between two JH response factors, which advances our understanding of the molecular mechanism of JH signaling.